Kobiety na bieżni do satysfakcjonujących relacji partnerskich i rodzinnych w kulturze celebrującej „Ja” - Ściupider-Młodkowska , Mirosława (Studia Edukacyjne, 2020)
The article aims at approximating the socio-cultural dimension of contemporary requirements of women, especially women who are socially imposed by the codes of self-improvement and satisfaction in almost every sphere of life: partnership, intellectual, family, sexual, aesthetic, professional. The article is divided into three parts. The first part, entitled “The run for liberation or alienation, narcissism and frustration”, discusses the evolution of the “Polish Mother” stereotype into that of the “superhero” type. The following part describes the conflict between women’s need for recognition and self-exclusion on their way to happiness. The last part designates the quest for recognition among items that satisfy the consumption hunger and escalate the hunger for recognition, simultaneously causing a natural disintegration of women’s inner power.